Identifikasi Tipe Stomata Pada Bebarapa Jenis Tumbuhan Dikotil Dan Monokotil: Identifikasi Tipe Stomata Pada Bebarapa Jenis Tumbuhan Dikotil Dan Monokotil - -, Ridwan; Hasidu, La Ode Abdul; Rumakefing, Hartina (Universitas Muslim Buton, 2022)
Stomata are clefts of the epidermis, each lined by two guard cells. In Greek, stoma means